Application Of Act No. 22 Of 2009 As A Traffic Accidents Countermeasures Management In The Blora Police Law Area - Preliyanto Puji Utomo; Bambang Tri Bawono (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2020)
The problems discussed in this study are efforts to tackle traffic accidents by law enforcers in the Blora Police Law Area and the application of Act No. 22 Of 2009 On Road Traffic and Transportation to accident rates in the Blora Police Law Area. The approach method used is sociological juridical, descriptive analytical research specifications. The data used are primary data and secondary data. Data collection methods are field studies and library studies. The data analysis method uses qualitative analysis. As a knife analysis, crime prevention theory and law enforcement theory are used. The results of the research show that the handling of traffic accidents by law enforcers in the Blora Police Law Area is carried out through preventive and repressive measures. Preventive efforts are carried out through routine patrol activities, zebra operations, counseling at schools and in the community and installing biilboard warning signs in accident-prone areas. The repressive effort is carried out through a series of investigative actions against traffic accidents which are guided by applicable laws and regulations. The application of Act No. 22 Of 2009 On Traffic and Road Transportation towards accident rates in the Blora Police Law Area is not optimal. The accident rate is still relatively high from year to year despite various efforts have been carried out. This is due to the lack of public awareness and legal culture of the community which does not support the programs implemented by the Blora Police Law Area in reducing the level of traffic accidents.Keywords: Implementation; Countermeasures; Traffic Accidents.